Flow-driven morphology control in the cobalt–oxalate system. Issue 12 (25th February 2016) - Tóth–Szeles, Eszter; Schuszter, Gábor; Tóth, Ágota; Kónya, Zoltán; Horváth, Dezső
Abstract : The presence of fluid flow by maintaining the density gradient and controlling the flow rate provides a simple method to modify the microstructure of cobalt oxalate. Abstract : The interaction of spatial concentration gradients with chemical reactions can lead to intricate precipitate patterns. When the density difference between the reactants is sufficient, gravity current forms at the reactive interface and solid particles can sediment along radially oriented thin lines if both nucleation and crystal growth are slow. In this paper, we have studied the flow-driven Co(ii )–oxalate system, by pumping cobalt nitrate solution into a thin layer of sodium oxalate solution. The formed precipitate consists of cobalt(ii ) oxalate tetrahydrate, identified by thermogravimetric and X-ray diffractometric analysis. This simple flow method to maintain the spatial gradients represents a controlled synthesis resulting in microstructures significantly different from those obtained in well-stirred homogeneous experiments.